A Phase 2 Randomized Trial of DCL-101, a Novel Pill-Based Colonoscopy Prep, vs 4L Polyethylene Glycol-Electrolyte Solution. Issue 12 (20th December 2020) - Bachwich, Dale R.; Lewis, James D.; Kowal, Vera O.; Jacobson, Brian C.; Calderwood, Audrey H.; Kochman, Michael L.
Abstract : INTRODUCTION: DCL-101, a novel Pill Prep, is compositionally identical to standard 4L polyethylene glycol-electrolyte solution (PEG-ELS) and delivers the salt encapsulated, with PEG 3350 coadministered as a taste-free oral solution. The aim of this study was to compare the safety, taste, and tolerability of DCL-101 with 4L PEG-ELS in outpatients preparing for colonoscopy, with a secondary objective to assess efficacy. METHODS: This was a multicenter, randomized, investigator-blinded, phase 2 clinical trial of 45 adult patients undergoing outpatient colonoscopy. Patients were randomized 2:1 to either DCL-101 (3L in cohort 1; 4L in cohort 2) or 4L PEG-ELS, each administered with split dosing. Safety was assessed over 3 post-treatment clinic visits. Tolerability was measured using the Lawrance Bowel-Preparation Tolerability Questionnaire and the Mayo Clinic Bowel Prep Tolerability Questionnaire. Efficacy was determined by expert central readers, blinded to treatment, using the Ottawa Bowel Preparation Quality Scale, Boston Bowel Preparation Scale, and Aronchick scale. RESULTS: Both DCL-101 doses had superior taste and tolerability relative to 4L PEG-ELS. All adverse events were grade 1 with no significant differences in adverse events among the 3 regimens. There were no significant differences in efficacy among the 3 treatments as defined by the centrally read Ottawa Bowel Preparation Quality Scale, Boston Bowel Preparation Scale, or Aronchick scores. There were no inadequate preps as judged by the site endoscopist. DISCUSSION: DCL-101 Pill Prep is a novel strategy that vastly improves the taste and tolerability of PEG-ELS solutions with safety and efficacy comparable with split-dose 4L PEG-ELS solutions.